International air passenger transport in the future - David Gillen (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
The objective of this paper is relatively straightforward, suggesting 'what international air passenger travel will look like in five, ten or fifteen years and why?' This requires answering two questions; what will be the principal determinants of the growth in international air travel and what impact will each of these drivers have on the growth rate? An imbedded question is does history have anything to teach us or are there new forces at work? Canvassing the current aviation trade press finds two schools of thought, one taking the position that this a deep recession but a recession nonetheless and once world economies start recovering air traffic will go back to the typical growth of 4-5 percent annually. A second school is less sanguine, taking the position that it will not be business as usual when economies stop sinking and move to recovery. Any economic recovery is going to involve fundamental changes in institutions, rethinking polices regarding government participation in economies and changes in economic leadership in the world. There is also the hydra of protectionism most prominent now in the US but certainly being practiced elsewhere, and what will happen to foreign ownership restrictions that prior to 2009 were being seen as hurting rather than helping world airlines. All of this will change international aviation going forward.
Keywords: 330